Precise targeting of cancer metastasis using multi-ligand nanoparticles incorporating four different ligands. Issue 15 (5th April 2018) - Peiris, P. M.; He, F.; Covarrubias, G.; Raghunathan, S.; Turan, O.; Lorkowski, M.; Gnanasambandam, B.; Wu, C.; Schiemann, W. P.; Karathanasis, E.
Abstract : A multi-ligand nanoparticle accounts for tumor heterogeneity, which includes targetable receptors that are continuously changing over time and space. Abstract : Metastasis displays a highly heterogeneous cellular population with cancer cells continuously evolving. As a result, a single-ligand nanoparticle cannot account for the continuously changing expression of targetable biomarkers over time and space. To effectively direct nanoparticles to metastasis, we developed a multi-ligand nanoparticle by using four different types of ligands on the same nanoparticle that target biomarkers on the endothelium associated with metastatic disease. These vascular targets included αv β3 integrin, P-selectin, EGFR and fibronectin. Using terminal and in vivo imaging studies, the targeting performance of the multi-ligand nanoparticles was compared to the single-ligand nanoparticle variants. All four single-ligand nanoparticle variants achieved significant targeting of lung metastasis in the 4T1 mouse model of breast cancer metastasis with about 2.5% of the injected dose being deposited into metastasis. A dual-ligand nanoparticle resulted in a nearly 2-fold higher deposition into lung metastases than its single-ligand counterparts. The multi-ligand nanoparticle significantly outperformed its targeting nanoparticle counterparts achieving a deposition of ∼7% of its injected nanoparticles into lung metastases. Using the high sensitivity of radionuclide imaging, PET imaging showed that a multi-ligand nanoparticle labeled with [ 18 F]fluoride was able to precisely target metastatic disease at its very early stage of development in three different animal models of metastatic breast cancer.